Analysis of the Implementation of Differentiated Learning in Elementary Schools: A Literature-Based Qualitative Study - Ronny Mugara; Enjang Yusup Ali (Universitas PGRI Yogyakarta, 2026)
This study aims to analyze the implementation of differentiated learning in elementary schools through a qualitative literature review approach and to offer a conceptual contribution to existing scholarship on differentiated instruction (DI) within the Indonesian educational context. Using thematic analysis, the study systematically reviewed national and international articles published between 2020 and 2025, focusing on coding, categorizing, and synthesizing recurring patterns related to content, process, and product differentiation. Synthesising the literature led to the development of a conceptual framework illustrating the interaction among teacher readiness, instructional design, school support systems, and digital resource integration as core components shaping the effective implementation of DI. The findings highlight several novel insights, including the identification of digital-supported differentiation as an emerging practice and the articulation of collaborative teacher learning communities as a structural enabler for sustainable DI practices. This study provides practical implications for educators, policymakers, and school leaders, particularly in strengthening professional development programs, designing supportive school policies, and integrating adaptive learning resources to optimise student-centred learning in the Merdeka Curriculum era. Keywords: differentiated learning, elementary school, independent curriculum, literature study, adaptive learning strategies